2017
DOI: 10.1016/j.reprotox.2016.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of orofacial clefting II: Effects of 5-Aza-2′-deoxycytidine on gene methylation during development of the first branchial arch

Abstract: Defects in development of the secondary palate, which arise from the embryonic first branchial arch (1-BA), can cause cleft palate (CP). Administration of 5-Aza-2′-deoxycytidine (AzaD), a demethylating agent, to pregnant mice on gestational day 9.5 resulted in complete penetrance of CP in fetuses. Several genes critical for normal palatogenesis were found to be upregulated in 1-BA, 12 hours after AzaD exposure. MethylCap-Seq (MCS) analysis identified several differentially methylated regions (DMRs) in DNA extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…We did not find such a simple relationship between methylation and expression with the other genes. The fact depressed methylation of the respective gene promoter regions did not correlate with the upregulation of these, has already been described for both HMAs [ 57 , 58 ]. In addition, increased expression of the respective genes after AZA or DAC treatment can be explained by a decrease in the methylation of their promoter regions in only a small number of cases.…”
Section: Discussionmentioning
confidence: 64%
“…We did not find such a simple relationship between methylation and expression with the other genes. The fact depressed methylation of the respective gene promoter regions did not correlate with the upregulation of these, has already been described for both HMAs [ 57 , 58 ]. In addition, increased expression of the respective genes after AZA or DAC treatment can be explained by a decrease in the methylation of their promoter regions in only a small number of cases.…”
Section: Discussionmentioning
confidence: 64%
“…To explore this idea more comprehensively, Methyl Capture-Seq was performed to assess the epigenome of 1-BAs exposed in utero for 12-hr to AzaD or vehicle. The results of this analysis are presented in a following study [94]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, to more comprehensively assess the demethylating effects of AzaD on the 1-BA epigenome, MethylCap-Seq (MCS) analysis was performed and the results of AzaD-treated 1-BAs were compared to that of vehicle-treated 1-BAs. Findings from this study are presented separately [94]. …”
Section: Discussionmentioning
confidence: 99%
“…However, CpG methylation analysis of select genes revealed that these observed changes in gene expression were likely not due to direct methylation changes at their respective loci. This was confirmed in the companion study utilizing MethylCap‐Seq (MCS) analysis in a similar experimental design, although hypomethylation of genes associated with cleft palate was observed, including Axin2 , Efna5 , and Hic2 (Seelan et al, 2017). Interestingly, despite these findings, the latter study identified several differentially methylated regions (DMRs) within endogenous viral elements.…”
Section: Epigenetic Mechanisms Of Orofacial Cleftsmentioning
confidence: 68%